FORMATION OF SECURITY OF THE ROAD ECONOMY ENVIRONMENT - Богінська, Людмила (SWorldJournal, 2024)
The article is devoted to the development of proposals for the formation of an effective organizational and economic mechanism of the road sector, which must meet the environmental safety requirements. Among them, functioning within the framework of the c